Students' Attitudes To Learning Mathematics With Technology In Rural Schools In Sabah - Chin, Sporty, Kin Eng; Crispina Gregory K Han Crispina Gregory K Han; Vincent Pang; Lay, Yoon Fah; Denis Lajium (2009)
The purpose of this study was to determine secondary schools students' attitudes to teaming Mathematics with technology in rural schools in Sabah. In this study, the focus of technology is computer. This study involved 17 secondary schools in Sabah. These schools were rural schools and non rural schools. A total of 633 students from form 4, form 2 and form 1 were chosen randomly as respondents of this study. Descriptive statistics and inferential "statistics were used to analyze the collected data. The reliability of the instrument was analyzed by using Reliability Analysis in the Statistical Package for Social Science (SPSS) 13. 0 for windows software. According to the analysis performed by using descriptive statistics such as frequency and percentage, it Is discovered that only 13.0% of students from rural schools possessed positive attitude to teaming Mathematics with technology whereas 21.5% of students from non rural schools possessed positive attitude to learning Mathematics with technology. Results of hypothesis testing by using T test has indicated that there is significant difference (t=-2.424, df=543, p<0.05) in students' attitudes to learning Mathematics with technology between rural schools and non rural schools. Students from non rural schools possessed higher confidence with technology compared to students from rural schools. Besides, results of analysis also showed that there is no significant difference in students' attitudes to learning Mathematics with technology based on gender, streaming and level of schooling. Five key concepts which were measured in this study i.e. attitude to teaming Mathematics with technology, confidence with technology, Mathematics confidence, affective engagement and behavioral engagement were proven to have correlations among each other.